2016
DOI: 10.1002/mrd.22762
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of BRG1 and histone demethylases, and aberrant H3K4 methylation in less developmentally competent embryos at the time of embryonic genome activation

Abstract: Epigenetics is a fundamental regulator underlying many biological functions, such as development and cell differentiation. Epigenetic modifications affect key chromatin regulation, including transcription and DNA repair, which are critical for normal embryo development. In this study, we profiled the expression of epigenetic modifiers and patterns of epigenetic changes in porcine embryos around the period of embryonic genome activation (EGA). We observed that Brahma-related gene 1 (BRG1) and Lysine demethylase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 60 publications
0
14
0
1
Order By: Relevance
“…Between the CP and DP Under the same feeding regime and environmental conditions, the first calving age of the CP was 51 days older than the DP, and the litter size of the CP was four piglets less and two live piglets less than the DP in the first two parities and in the first three parities, respectively ( Table 3). DNA methylation was a common epigenetic modification and affected oocyte meiotic maturation and embryonic development, which in turn affecting the litter size Glanzner et al, 2017;Hwang et al, 2017a;. In this study, we found that the level of methylation and the methylated functional regions of the same tissue between the two pigs were different.…”
Section: Phenotype and Methylation Were Differentmentioning
confidence: 51%
“…Between the CP and DP Under the same feeding regime and environmental conditions, the first calving age of the CP was 51 days older than the DP, and the litter size of the CP was four piglets less and two live piglets less than the DP in the first two parities and in the first three parities, respectively ( Table 3). DNA methylation was a common epigenetic modification and affected oocyte meiotic maturation and embryonic development, which in turn affecting the litter size Glanzner et al, 2017;Hwang et al, 2017a;. In this study, we found that the level of methylation and the methylated functional regions of the same tissue between the two pigs were different.…”
Section: Phenotype and Methylation Were Differentmentioning
confidence: 51%
“…It has been reported that many different epigenetic modifications can change the structure of chromatin and participate in the regulation of gene expression and nuclear reprogramming during SCNT [26,27]. However, there is no clear consensus about how the DNA methylation pattern linked to the histone modifications and how the complex epigenetic information is integrated and translated into defined chromatin structures and gene expression level.…”
Section: Discussionmentioning
confidence: 99%
“…Histone lysine methyltransferases (KMTs) and KDMs enzymes regulate gene expression by modulating histone methylation levels [17]. Among all the histone modifications, the methylation levels of lysines 4, 9 and 27 in histone 3 are the most studied and have been shown to regulate embryo development and EGA transition [18][19][20][21][22][23], as well as cell differentiation and reprogramming [24][25][26][27][28]. Moreover, functional studies revealed that active removal of epigenetic marks is crucial for embryo development.…”
Section: Introductionmentioning
confidence: 99%